Real-World Clinical Outcomes of Biosimilar Trastuzumab (CT-P6) in HER2-Positive Early-Stage and Metastatic Breast Cancer - Bae, Soong June; Kim, Jee Hung; Ahn, Sung Gwe; Jeung, Hei-Cheul; Sohn, Joohyuk; Kim, Gun Min; Kim, Min Hwan; Kim, Seung Il; Park, Seho; Park, Hyung Seok; Kim, Ji Ye; Jeong, Joon (Frontiers in Oncology, 2021)
Background: The trastuzumab biosimilar CT-P6 has demonstrated equivalent efficacy and comparable safety to reference trastuzumab (RTZ) in clinical trials of human epidermal growth factor receptor 2 (HER2)-positive early breast cancer (EBC). Here, we present the first real-world comparison of CT-P6 versus RTZ with dual HER2-targeted therapy for the neoadjuvant and palliative first-line treatment with HER2-positive EBC and metastatic breast cancer (MBC) patients in two tertiary hospitals in Korea. Methods: We retrospectively investigated medical records in the Severance Breast Cancer Registry in Korea. We identified patients with HER2-positive EBC (n=254) who had received neoadjuvant chemotherapy with RTZ or CT-P6, plus pertuzumab, carboplatin and docetaxel (TCHP) and untreated stage IV MBC (n=103) who had received palliative first-line treatment with RTZ or CT-P6, plus pertuzumab and docetaxel (THP) between May 2014 and December 2019. The primary endpoints were pathologic complete response (pCR) in the EBC and progression-free survival (PFS) in the MBC cohort. Overall survival (OS), overall response rate (ORR), disease control rate (DCR), and cardiac safety were secondary endpoints. Results: A similar percentage of EBC patients achieved a pCR with CT-P6 versus RTZ (74.4% [93/125]) vs 69.8% [90/129], p=0.411). For patients with MBC, median follow-up duration was 23.0 and 41.0 months for CT-P6 and RTZ groups, respectively; median PFS did not differ significantly between two groups (13.0 vs 18.0 months, 95% confidence intervals (CIs) 0.0-26.6 vs 11.3-24.7, p=0.976). The ORR, DCR, and cardiac safety profiles did not also show significant difference efficacy outcomes between two groups. Conclusions: These real-world data suggest that biosimilar trastuzumab CT-P6 has similar effectiveness and cardiac safety to RTZ in HER2-positive EBC and MBC patients, when administered as part of dual HER2-targeted therapy with pertuzumab plus chemotherapy in the neoadjuvant or palliative setting.